2011
DOI: 10.1002/ana.22329
|View full text |Cite
|
Sign up to set email alerts
|

Activation of central trigeminovascular neurons by cortical spreading depression

Abstract: Objective-Cortical spreading depression (CSD) has long been implicated in migraine attacks that begin with visual aura. Having shown that a wave of CSD can trigger long-lasting activation of meningeal nociceptors -the first-order neurons of the trigeminovascular pathway thought to underlie migraine headache -we now report that CSD can activate central trigeminovascular neurons in the spinal trigeminal nucleus (C1-2).Methods-Stimulation of the cortex with pin prick or KCl granule was used to induce CSD. Neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
274
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(299 citation statements)
references
References 62 publications
(120 reference statements)
10
274
2
Order By: Relevance
“…On the other hand, there is experimental animal evidence that CSD might activate the trigeminal sensory system, presumably by depolarizing perivascular trigeminal terminals at meningeal and dural blood vessels (Haerter et al 2005, Ayata et al 2006, Bolay et al 2002. Zhang et al (2010Zhang et al ( , 2011 demonstrated, for the first time, that the induction of CSD by focal stimulation in vivo of the rat visual cortex can lead to long-lasting activation of the nociceptors innervating the meninges in the trigeminal ganglion.…”
Section: Migraine and Familial Hemiplegic Migraine (Fhm)mentioning
confidence: 99%
“…On the other hand, there is experimental animal evidence that CSD might activate the trigeminal sensory system, presumably by depolarizing perivascular trigeminal terminals at meningeal and dural blood vessels (Haerter et al 2005, Ayata et al 2006, Bolay et al 2002. Zhang et al (2010Zhang et al ( , 2011 demonstrated, for the first time, that the induction of CSD by focal stimulation in vivo of the rat visual cortex can lead to long-lasting activation of the nociceptors innervating the meninges in the trigeminal ganglion.…”
Section: Migraine and Familial Hemiplegic Migraine (Fhm)mentioning
confidence: 99%
“…Cortical spreading depression is the electrophysiological manifestation of aura in the cerebral cortex thought to activate the trigeminovascular system and ultimately provoke headache. Controversy exists as to whether this process happens through CGRP release from peripheral trigeminal terminals [34,108,109]. Studies in rats showed endogenous release of CGRP during extracellular hyperkalemia-induced cortical spreading depression and inhibition of this phenomena by CGRP-RAs [110].…”
Section: Migraine and Auramentioning
confidence: 99%
“…Such neurogenic inflammation is thought to trigger a headache via stimulation of trigeminal afferents. Consistent with this hypothesis, cortical SD induced intracranial neurogenic inflammation around the meningeal blood vessels [13][14][15] , and subsequent activation of both peripheral [16] and central [17] trigeminal nociceptive pathways has been described. Here, we review the experimental evidence mainly from neurophysiological studies that has advanced the understanding of whether and how the neurovascular phenomenon of cortical SD causes intracranial neurogenic inflammation, and subsequently participates in triggering a migraine headache.…”
Section: Introductionmentioning
confidence: 55%
“…However, it is still controversial whether the neurogenic inflammation induced by cortical pathway, is significantly increased by cortical SD, and this increase is abolished by trigeminal rhizotomy [56] . Moreover, cortical SD-evoked single neuron activity in the trigeminal ganglion (peripheral pathway) and the TNC has also been demonstrated directly by electrophysiological studies [17] . Such activation was observed as a two-fold increase in ~50% of neurons in the trigeminal ganglion and TNC, and persisted for 45 min or longer.…”
Section: Cortical Sd Activates the Trigeminal Nociceptive Pathway Inmentioning
confidence: 97%